Anterior chamber paracentesis cytology (cytospin technique) for the diagnosis of intraocular lymphoma. Issue 6 (17th February 2006) - Finger, P T; Papp, C; Latkany, P; Kurli, M; Iacob, C E
Abstract : Aim: To report on the diagnosis of intraocular lymphoma by aqueous cytology. Methods: Four patients suspected of having intraocular lymphoma were evaluated by anterior chamber (AC) paracentesis with cytology (cytospin technique). All had a history of non-ocular lymphoma and presented with at least one plus anterior chamber cells despite intensive glucocorticoid therapy. A 25 gauge needle was inserted through clear cornea (bevel up), over the iris stroma, so as to drain the AC. The aqueous humour was sent for cytopathology (cytospin technique), culture, and sensitivity tests. Results: All procedures were diagnostic. Three were lymphoma and the fourth was culture positive for Propionibacterium endophthalmitis. No secondary glaucoma, hyphaema, cataract or infections were related to AC paracentesis. Conclusions: In this series, AC aspiration cytology enhanced by the cytospin technique was an effective, minimally invasive alternative to vitrectomy based biopsy. This technique should be considered to rule in the diagnosis of intraocular lymphoma in selected cases with cells in the anterior chamber.